SISTEM PAKAR PENENTUAN PASAL PERLINDUNGAN PEREMPUAN BERBASIS WEBSITE DENGAN METODE FORWARD CHAINING (STUDI KASUS PENGADILAN NEGERI BANGIL) - Kurniawan Wahyu Haryanto; Zahroh Azmil Fitriani (SPIRIT, 2023)
Abstract: Bangil District Court An agency that has a function as an enforcer of justice that requires information quickly, especially in determining articles. so it requires a system that will make it easier to determine the articles that have been obtained based on the data and acknowledgment by the reporting party described in the system. The method used in this research is the forward chaining method. Where data collection si done through literature study and interviews. The result of this research is an application that can make it easier for the court to determine the article on women’s protection quickly, accurately and precisely.